Nutrition program effect on soccer players - Perrotta, F. (Journal of Human Sport & Exercise, 2019)
This paper is designed to help coaches and educators in their mission, reporting different knowledge based, as well as on the most classic consensus theories, on the most up-to- date scientific acquisitions about the most appropriate way to feed and organize their nutrition before, during and after a part or a training session. The text will be deliberately concise, but the bibliographic sources added as reference, portrayed in the international scientific literature, will constitute an ulterior study opportunity for those wishing to deepen each single topic.